2004
DOI: 10.1007/s00436-003-1055-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of the recombinant Theileria annulata surface protein in an indirect ELISA for the diagnosis of tropical theileriosis

Abstract: The recombinant surface protein of Theileria annulata (TaSP) was used in the standardization and validation of an enzyme linked immunosorbent assay (ELISA) for the detection of circulating antibodies against tropical theileriosis. ELISA data were expressed as the percentage positivity (PP) of the reactivity of an internal positive control. A total of 50 sera samples from a disease-free area were used for the calculation of the cut-off value which served as a threshold between the positive and the negative sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 7 publications
1
48
0
Order By: Relevance
“…Eight sera samples, which showed PP above the cut off value, were judged as negative by the IFAT, which indicated that the ELISA might have been more efficient in diagnosing lower antibody titers than the IFAT. On the other hand, there was no correlation observed between the values of the IFAT titers and ELISA PP, as (Gubbels et al 2000;Bakheit et al 2004). This behavior could be attributed to individual variations in the animals' reactions against the single proteins (including the test protein) present in the panel of antigens (schizont antigens) used in the IFAT.…”
Section: Discussionmentioning
confidence: 62%
“…Eight sera samples, which showed PP above the cut off value, were judged as negative by the IFAT, which indicated that the ELISA might have been more efficient in diagnosing lower antibody titers than the IFAT. On the other hand, there was no correlation observed between the values of the IFAT titers and ELISA PP, as (Gubbels et al 2000;Bakheit et al 2004). This behavior could be attributed to individual variations in the animals' reactions against the single proteins (including the test protein) present in the panel of antigens (schizont antigens) used in the IFAT.…”
Section: Discussionmentioning
confidence: 62%
“…It codes for a protein of about 315 amino acids and has a predicted molecular weight of 36 kDa. Recently, Bakheit et al (2004) applied this antigen in an indirect ELISA for the diagnosis of tropical theileriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme immunoassays based on soluble piroplasm antigen can be used for large scale detection of theileriosis in the field but it is difficult to standardize the test from crude parasite material, and there is always the requirement of experimental animals for parasite production (Manuja et al 2000). To over come these problems, recombinant antigens of Theileria (Gubbels et al 2000;Illhans et al 1998;Williamson et al 1989;Bakheit et al 2004) were used with variable success. This paper communicates the use of recombinant merozoite surface antigen of an Indian isolate of T. annulata to determine the serological response in apparently healthy cattle in the field.…”
Section: Introductionmentioning
confidence: 99%